Staff Confidence in Supporting Student Mental Health: Outcomes from a Survey - Ellice Whyte; Helen Payne; Bruce Hajilou (MDPI AG, 2024)
(1) Background: The number of university students experiencing mental health problems has been a growing concern over recent decades, and support for them is now considered an inevitable part of the role of an academic. Research into the role of the academic reveals ambiguous expectations and weak support regarding their pastoral responsibilities, leading to a lack of confidence when dealing with student mental health concerns. (2) Methods: Following previous research, the present preliminary study employed an online survey (N = 43) in three schools at a university in the East of England to identify academics' current confidence in supporting student mental health. This addressed four subscales: (i) identifying mental health concerns in students, (ii) approaching and discussing mental health concerns with students, (iii) academics' knowledge concerning the central support services available within the university, and (iv) academics' skills in providing ongoing support for student mental health and wellbeing. (3) Results: Female respondents scored higher than males on their knowledge concerning the central student mental health support services within the university, and 60+-year-old lecturers were least confident in identifying mental health concerns compared to 40-49- and 50-59-year-olds. (4) Conclusions: Recommendations for interventions include mental health awareness training, policy development, and a precise and nuanced description of an academic's pastoral role and responsibilities to ensure that students receive appropriate and sufficient psychological support.